Music Therapy as a supporting method in the treatment of bipolar disorder - Woszczyńska, Oliwia Brygida; Wojciechowska, Agnieszka Ewelina; Molenda, Marek Jarosław; Wachowska, Maria; Szymura, Marta; Paniak, Mateusz; Romaniuk, Mateusz; Krawczyk, Michał Brunon; Rycąbel, Paweł Maciej; Sowiński, Wojciech Jan (Journal of Education, Health and Sport, 2025)
Bipolar disorder is a mental illness that affects people of all ages and both sexes equally. Psychiatry primarily relies on conventional treatments such as pharmacotherapy, electroconvulsive therapy, and psychotherapy to manage bipolar disorder. However, despite their effectiveness and many benefits, these methods may not always be sufficient—especially in treatment-resistant cases. Music therapy, an evidence-based therapeutic approach used in psychology, psychiatry, neurology, rehabilitation, and other fields, influences individuals' well-being through active and receptive techniques. The aim of this article is to review available studies and examine the effectiveness of music therapy in the treatment of bipolar disorder. This review explores its role in conjunction with pharmacotherapy, ketamine infusions, and electroconvulsive therapy. Furthermore, the purpose of this article is to assess whether there are enough reliable studies to determine if music therapy is an effective supportive treatment.